Physico-chemical, photo-catalytic and O-2-adsorption properties of TiO2 nanotubes coated with gold nanoparticles - Malwadkar, Sachin S.; Gholap, Ramkrishna S.; Awate, Shobhana V.; Korake, Prakash V.; Chaskar, Manohar G.; Gupta, Narendra M. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Gold-containing titania nanotubes (Au/NT) were found to display higher activity for photooxidation of acetaldehyde, as compared to corresponding gold-free nanotubes and also a Degussa P-25 catalyst. Besides CO2 as a major reaction product, small amounts of H-2, CH4, CO, H2O and CH3COOH were also formed, irrespective of the catalyst employed. High-resolution TEM examination showed that most of the gold particles in Au/NT were of 1.5-5 nm size, distributed both within and at outside surface of the nanotubes. Some larger size (10-70 run) clusters were also seen at the external surfaces, particularly in the samples calcined at an elevated temperature. The temperature-programmed desorption measurements revealed that, compared to P-25 TiO2, a significant entrapment of O-2 occurred at two distinct tubular sites of NT samples, corresponding activation energy of desorption (E,) being around 36 and 41 kcal mol(-1). On the other hand, gold nanoparticles in Au/NT served as independent low-energy (E-a = 26 kcal mol(-1)) sites for adsorption/activation of O-2. These adsorptive properties of TiO2 and Au were lost completely on calcination, thus revealing a crucial role played by the particle size. In situ IR spectroscopy results showed that room-temperature exposure to acetaldehyde + air gave rise to a molecularly bound state, i.e. CH3CHOad, over both NT and Au/NTsamples, which in turn transformed quickly to yield certain acetate (CH3COOad-) and formate (HCOOad-) type transient species with the involvement of the surface OH groups. The decomposition and oxidation of these surface species with the help of O-2(-), O-ad and hydroxyl ion radicals (OH-) formed at photo-excited Au/NT interfaces led to the reaction products mentioned above. We conclude that, besides electron-hole charge separation, the adsorptive properties of host matrix and nanosize gold may together play a significant role in deciding the photo-catalytic properties of Au/TiO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Acetaldehyde oxidation; Gold co-catalyst; O-2-adsorption; Photo-catalytic activity; TiO2 nanotubes

Photocatalytic degradation of phosphamidon using Ag-doped ZnO nanorods - Korake, Prakash V.; Sridharkrishna, R.; Hankare, P. P.; Garadkar, K. M. (Toxicological and Environmental Chemistry, 2012)
The photocatalytic degradation of the organo-phosphorous pesticide phosphamidon at low concentration in aqueous solution on Ag-doped ZnO nanorods was investigated. Nanosized Ag-doped ZnO rods were synthesized by using a microwave assisted aqueous method. High molecular weight polyvinyl alcohol was used as a stabilizing agent. Composition and structure were investigated using energy-dispersive X-ray spectroscopy (EDAX) and X-ray diffraction (XRD). The XRD pattern reveals that ZnO nanorods are of hexagonal wurtzite structure. The average crystallite size calculated from Scherrer's relation was found to be 30 nm. The effects of catalyst loading, pH value, and initial concentration of phosphamidon on the photocatalytic degradation efficiency using Ag-doped ZnO nanorods as a photocatalyst have been discussed. The results revealed that Ag-doped ZnO nanorods with a diameter of 30 nm showed highest photocatalytic activity at a surface density of 1 g dm(-3). The catalyst doped with 0.2 mol% Ag is effective for the degradation of phosphamidon with visible light. This opens a new possibility to decompose pesticides that are present in wastewater.
Keywords: Ag-doped zinc oxide; phosphamidon; Photocatalysis; Photodegradation

Genesis of enhanced photoactivity of CdS/Ni-x nanocomposites for visible-light-driven splitting of water - Devi, Suman; Korake, Prakash V.; Achary, Srungarpu N.; Gupta, Narencira M. (International Journal of Hydrogen Energy, 2014)
A series of CdS/Ni-x nanocomposite photocatalysts, containing ca. 0.6-15 wt% Ni, were synthesized using a one-step hydrothermal method and characterized for their crystallographic, morphological, interfacial, and optical properties. Rietveld refinement of powder XRD data revealed the coexistence of wurtzite (hexagonal) and zinc blende (cubic) phases of CdS in ratios dependent on Ni content. Only a fraction of Ni existed as a secondary phase of NiS while the majority occupied the lattice positions of hexagonal CdS. Whereas up to 10-fold enhancement in H-2 evolution compared with pure CdS was observed for samples containing similar to 1.5-4.5 wt% Ni, samples with smaller or larger Ni content displayed poor activity for visible-light-induced splitting of water in presence of sulfide-sulphite ions as sacrificial electron donors. In contrary to recent findings, our study reveals that the enhanced CdS photoactivity is not a result of charge transfer between p-type NiS and n-type CdS, Ni-induced visible-region absorbance, or the coating of CdS particles by non-photoactive NiS. Instead, the preparation-dependent hexagonal/cubic CdS phase boundaries and particle morphology may play a crucial role. Additionally, certain Ni-doping-induced sub-bandgap shallow energy levels contribute to charge carrier separation. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CdS/Ni-x nanocomposites; Dominant hexagonal facets; Enhanced photoactivity; Hydrogen evolution; Phase boundary effects; water splitting

Role of aliovalent cation doping in the activity of nanocrystalline CdS for visible-light-driven H-2 production from water - Korake, Prakash V.; Achary, Srungarpu N.; Gupta, Narendra M. (International Journal of Hydrogen Energy, 2015)
This study was aimed at discerning the enhancement in the visible-light-driven water splitting activity of nanocrystalline CdS photocatalysts because of their doping with a small amount of an aliovalent cation (Ag+ or Cr3+). The CdS/Cr-x (x = 0-2.3 wt%) and CdS/Ag-x (x = 0-1.5 wt%) samples, which were synthesized using a one-step hydrothermal method, were characterized systematically for their crystallographic, morphological, interfacial, and photo-physical properties. The Rietveld refinement of the powder X-ray diffraction data enabled us to quantify the doping-effect on the phase composition and lattice parameters. As compared to pure CdS, the samples containing similar to 0.2 wt% of Cr or Ag showed two or tenfold enhancement in the rate of H-2 evolution from water, respectively, when sulfide-sulfite ions were used as sacrificial electron donors. This pyramidal trend, i.e. maximum activity for a specific impurity content, which decreased on decreasing as well as increasing the amount of doping, did not occur owing to the presence of a secondary-phase metal sulfide or a dispersed metal cocatalyst. Our study revealed that instead of the widely advocated mechanism involving inter-semiconductor or semiconductor-to-metal electron transfer steps, the doping-modified photoactivity of CdS was governed by certain bulk and surface properties such as the cation-dependent particle nucleation, dominance of hex-CdS facets, and structural defects. Additionally, impurity-induced sub-bandgap charge-trapping states also contributed to the overall quantum efficiency. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.

Quenching effect of uranyl species in the photoluminescence emission and visible-light-driven water dissociation activity of CdS and TiO2 photocatalysts - Gupta, Narendra M.; Kelkar, Sarika A.; Korake, Prakash V. (Photochemical & Photobiological Sciences, 2016)
Anchoring of uranyl species (2-4 mol%) led to the complete quenching of photoluminescence emission and the visible-light-driven water photodissociation activity of TiO2 (Degussa-P25) and a hydrothermally synthesized CdS photocatalyst. Photophysical measurements revealed a fast relaxation and the transfer of photogenerated electrons/energy from the TiO2 or CdS substrate to the acceptor uranyl moieties. Besides the position of flat band levels, significant overlap of the absorption/emission spectra of the host matrix and the surface-bound UO22+ species is responsible for this reverse energy transfer from a wide bandgap semiconductor to a material with a smaller band-to-band energy gap.